FACTORS INFLUENCING DKI JAKARTA CONSUMERS’ PURCHASE DECISIONS AT MCDONALD’S - Citamani, Nikita Louis; Firdausy, Carunia Mulya (Graduate Program of Universitas Tarumanagara, 2024)
Consumers’ decisions to buy fast food produced by McDonald’s are believed to be influenced by many factors. However, studies advanced in the literature that examine these factors are not well-documented. The purpose of this study was to determine whether or not brand awareness, brand image and emotional branding influence consumer purchasing decisions on McDonald’s products in DKI Jakarta. 100 survey responses were gathered via purposive sampling method. Questionnaire ditributed in Google Form by Social Media platform such as Whatsapp, Telegram and Instagram. Method to analyse the data was by using multiple linear regression method. The Result of this study indicates that Brand Awareness and Emotional Branding partially influence the Purchase Decision. In contrast, Brand Image showing no positive influence. However, Brand Awareness, Brand Image and Emotional Branding have positive influence to Purchase Decision of McDonald’s consumers in DKI Jakarta simultaneously. Therefore, McDonald’s should improve its Brand Awareness, Brand Image and Emotional Branding so that consumer decisions to buy their products in Indonesia continue to increase.